Review of the Cambrian Stratigraphy of the Argentine Precordillera - O. Bordonaro (Geologica Acta, 2003)
The Cambrian rocks of the Argentine Precordillera are analyzed and updated providing a new stratigraphic interpretation. The lithostratigraphic assemblages provide evidence that the Precordilleran Cambrian Basin was a rimmed platform. The lithostratigraphy record enables to distinguish three large areas corresponding to an inner platform, an outer platform to slope environment and a mixed zone where both platforms and the rim interfinger. The biostratigraphic proposal based on trilobites include restricted shelf biozones to the East, characterized by sparse, endemic and low diversity polymeroid faunules. Moreover, to the West outer shelf biozones are characterized by widespread, high diversity, mixed endemic and cosmopolitan polymeroid and agnostoid faunas. The lithostratigraphic and biostratigraphic data prove the existence of an important hiatus near the Lower-Middle Cambrian boundary, which is correlated to the Hawke Bay regressive event recorded along the eastern margin of Laurentia. The Olenellus Zone assemblage trilobites underlies the Glossopleura or the Ehmaniella Zone. The early Middle Cambrian zones (from Plagiura-Poliella to Albertella) are lacking in the whole Precordillera.